Let $\mu$ and $\sigma$ be constants and consider the SDE $dY(t)=\mu Y(t)dt+\sigma Y(t)dW(t)$ with $W(t)$ Brownian motion and $Y(0)=y_{0}$. Using the solution to the SDE, $Y(t)=y_{0}\exp[(\mu-\frac{\sigma^{2}}{2})t+\sigma dW(t)]$, I computed the expression $dY^{-1}(t)$ as following:

Define $S(t)=Y^{-1}(t)=y^{-1}_{0}\exp[(-\mu+\frac{\sigma^{2}}{2})t-\sigma dW(t)]$

If we rewrite this in the standard form we find:

$S(t)=s_{0}\exp[(\mu_{2}-\frac{\sigma^{2}_{2}}{2})t+\sigma_{2}dW(t)]$ with $\sigma_{2}=-\sigma$, $\mu_{2}=\sigma^{2}-\mu$ and $s_{0}=y^{-1}_{0}$ (assuming $y_{0}\neq0$).

which would imply that if we 'reverse' the SDE problem we find


Is this way of computing $dY^{-1}(t)$ correct?


Given that $\mu$, $\sigma^2$, were general, yes it's correct. You can also check using Ito.


Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.